Testes de desempenho de uma rede WAN utilizando o protocolos MPLS: uma análise prática - Romeo, Renan (2016)
This project had as an objective to implement a WAN network (Wide Area Network) integrating Headquarter and Branch in real time, using practical analysis. For the implementation MPLS protocol was utilized (Multiprotocol Label Switch) as well as VPN (Virtual Private Network). Utilizing a bibliographic survey that was carried out on computer networks with enfaces in WAN technology using MPLS protocols with all its components and functionalists as well as virtual private networks (VPN). After implementing the structure, three scenarios were established. For each scenario performance tests were ran to identify the behavior of the network in its worse conditions, seeking to maintain the network structure overloaded. All tests were documented and can be found within the worksheet. Through deep analyses of the results it was possible to come to a conclusion. When the network is overloaded it can cause failure sending and receiving packets. It was also found that by controlling packet traffic flow it is possible to maintain the network stability. However this should be both service provider and IT department of client requesting the service responsibility.